Display-centred applications in ubiquitous computing - José, Rui (2006)
Public displays can play an important enabling role in ubiquitous computing environments. This paper describes an on-going work for a multipurpose, multi-display infrastructure, designed to address the requirements of display-centred applications in ubiquitous computing environments. The system provides an infrastructure in which situated displays can act as portals to the physical space, allowing ubicomp applications to support their association with the physical world by providing them with display services and situationspecific user input and context information.